2021
DOI: 10.1080/21655979.2021.1915658
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal pentraxin II (NPTX2) hypermethylation promotes cell proliferation but inhibits cell cycle arrest and apoptosis in gastric cancer cells by suppressing the p53 signaling pathway

Abstract: Gastric cancer is a considerable health burden worldwide. DNA methylation, a major epigenetic phenomenon, is closely related to the pathogenesis of cancer. Neuronal pentraxin II (NPTX2) has been found to be hypermethylated in several cancers such as glioblastoma and pancreatic cancer. However, the roles of NPTX2 in gastric cancer have not been reported. To explore this issue, NPTX2 expression in gastric cancer cells was assessed by western blot and quantitative real-time polymerase chain reaction (qRT-PCR). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Applying CFG analysis and expression cross-validation in different brain regions, we identified six candidate risk genes for AD. NPTX2 belongs to the neuronal pentraxin family, whose promoter was frequently highly methylated in many solid tumors ( Park et al, 2007 ; Shukla et al, 2013 ; Rasmussen et al, 2017 ; Alholle et al, 2013 ; Xu et al, 2021a ). Decreased NPTX2 level has been reported to be associated with diverse neurological diseases, including Alzheimer’s disease, anxiety, vascular dementia, Parkinson’s disease and ischemia ( Moran et al, 2008 ; Chang et al, 2018 ; Cai et al, 2019 ; Shao et al, 2020 ; Libiger et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Applying CFG analysis and expression cross-validation in different brain regions, we identified six candidate risk genes for AD. NPTX2 belongs to the neuronal pentraxin family, whose promoter was frequently highly methylated in many solid tumors ( Park et al, 2007 ; Shukla et al, 2013 ; Rasmussen et al, 2017 ; Alholle et al, 2013 ; Xu et al, 2021a ). Decreased NPTX2 level has been reported to be associated with diverse neurological diseases, including Alzheimer’s disease, anxiety, vascular dementia, Parkinson’s disease and ischemia ( Moran et al, 2008 ; Chang et al, 2018 ; Cai et al, 2019 ; Shao et al, 2020 ; Libiger et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NPTX2 (neuronal pentraxin 2) is also a member of the highly conserved pentraxin protein group and was previously associated with neurodegenerative diseases [41]. Additionally, it was also previously observed that NPTX2 hypermethylation inhibits cell cycle arrest and apoptosis in gastric cancers via p53 suppression [42], which in turn suggests a possible association of NPTX2 with epigenetic regulation. Synaptic receptors CHRM2 (cholinergic receptor muscarinic 2) and DRD2 (dopamine receptor D2) have also been listed at significantly enriched terms in GO analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that the p53 signaling pathway plays a vital role in processes such as apoptosis and cell cycle regulation [ 32 , 33 ]. Current evidence suggests that p53 encodes a sequence-specific transcription factor that controls the expression of genes whose products (such as Bax; PUMA,p53-upregulated modulator of apoptosis) mediate apoptosis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%